How different are performance management systems? Empirical typology of performance management systems - Kadak, Tarmo; Laitinen, Erkki K. (Journal of Business Economics and Management, 2023)
The purpose of the research is to extract an empirical typology presenting the diverse types of PMSs. For creating empirical typology, a Two-Step cluster analysis was applied. The types of PMSs are characterized by the variables extracted from the chain model found in the literature. We discovered two relevant dimensions specifying the PMSs: the importance of strategy for the firms and the multitude of organizational levels. Based on these, we extracted four clusters (types) of PMS along the dimensions of strategy focusing and organizational level. The findings show that the most advanced PMSs are found in the Strategy-focused Multi-level cluster, before the Strategyfocused One-level cluster. We also linked the dimensions within the four aspects of PMSs: strategic, alignment and process, usage, and information aspects. We found that the expected success of PMSs is positively related to the strategy-focus and multiplicity of levels. These findings broaden the common typologies of PMS and add the intrinsic features of the firm to the types of PMS reflecting strategy orientation and the multitude of hierarchy levels of the firm.